RESOLUTION AND MANAGEMENT OF CONFLICTS IN THE CULTURES OF RUSSIA AND CHINA - Leonov, N.I.; Glavatskikh , V.G.; Glavatskikh M. M. М.М. (Modern Psychology, 2020)
The growing tension in the modern world obliges modern psychology to find ways to manage conflicts in such a way that the conflict itself is a controlled process, the outcome of which should be constructive, leading to the removal of contradictions and tensions in society. The article reveals the specifics of conflict management and the degree of influence of third parties in the conflict in the cultures of Russia and China. The roles of third parties in conflict management in different cultures are defined. The article considers culture as a system forming the consciousness of the individual, manifested in myths and legends of peoples.